The Effectiveness of Giving A Combination of Ginger and Papaya Powder Drink in Reducing the Frequency of Nausea and Vomiting in Pregnant Women 12-16 Weeks - Desi Ratna Sari; Yanti Herawati; Udin Sabarudin (GLOBAL HEALTH SCIENCE GROUP, 2026)
Nausea and vomiting that occurs in early pregnancy is a common occurrence, it is due to an increase in the hormones estrogen, progesterone and the release of the hormone HCG (humanchorionic gonadothropin). Nausea and vomiting occur between 4 – 8 weeks and will continue for 14 -16 weeks. If this is not handled properly, it will harm the mother and fetus, because of a decrease in appetite resulting in a lack of electrolyte balance such as sodium, calcium, and potassium. The purpose of this study is to determine the effectiveness of jederasa powder drink in reducing nausea and vomiting in pregnant women at 12-16 weeks in the working area of UPTD Tanjung Baru Health Center, Ogan Komering Ulu Regency. This research employed a quantitative approach in the form of a pre-experimental study with a one-group pretest-posttest design. One group underwent pre- and post-treatment testing. The study focused on pregnant women experiencing emesis gravidarum symptoms. Only one group received treatment, and the results were then observed. Sampling was conducted using a purposive sampling technique based on previously identified population characteristics. Thirty-three respondents experienced nausea and vomiting. The study was conducted for 14 days, from September 27 to October 10, 2024. Data analysis used a paired sample t-test. The administration of jederasa powder drink showed the results of the frequency of nausea was known, the value of the